Mechanism of Mining-Induced Dynamic Loading in Shallow Coal Seams Crossing Maoliang Terrain - Jie Zhang; Guang Qin; Tao Yang; Bin Wang; Yifeng He; Shoushi Gao (Applied Sciences)
To address the intense mining pressure and dynamic accidents, such as shield collapse during mining in shallow coal seams crossing the Maoliang terrain, this study focuses on Panel 30206 of the Yanghuopan Coal Mine. Through theoretical analysis, numerical simulation, and field measurements, the stress transfer patterns and dynamic changes in shield loads during mining were analyzed, and the mechanism of dynamic mining pressure and calculation method for maximum support resistance were determined. The results show that when the working face enters the load-affected zone of the Maoliang terrain, the base load ratio of the overburden increases. The fracturing of the roof strata causes a synchronized motion between the key stratum and the overlying surface layer. The fracture and instability of the key stratum under mining-induced terrain loads significantly increase the shield resistance and intensify the mining pressure, with a hysteresis effect. Field measurements indicate a maximum shield working resistance of 8974 kN at Panel 30206, showing a 3.25% deviation from the theoretical value of 9266 kN, with a 25 m lag behind the peak load in the Maoliang terrain. This research provides criteria for support selection and ground control in Maoliang terrain mining, ensuring safe production.